Diabetes Compliance Management Revolution in Indonesia: Uncovering the Latest Trends in Continuous Glucose Monitoring (CGM) Usage - Dwight Mahaputera Marulitua Hutapea (PT. Anagata Sembagi Education, 2025)
The prevalence of diabetes in Indonesia continues to increase along with changes in the lifestyle of urban communities who are less active and consume high-sugar and fat foods. Low awareness of early detection and minimal patient compliance with blood glucose monitoring are major challenges in managing this disease. This study uses a qualitative approach with a phenomenological method to explore the subjective experiences of diabetes patients in using Continuous Glucose Monitoring (CGM) technology. The results of the study show that CGM is not only a real-time glucose monitoring tool, but also a trigger for behavioral transformation, self-empowerment, and increased patient compliance. However, structural challenges such as the high price of the device, the fact that CGM has not been guaranteed by BPJS, low digital literacy, and the gap in access between the upper and lower middle economic groups still hinder the widespread implementation of this technology. The adoption of CGM in Indonesia tends to be limited to certain groups, and has not become an integrated national strategy. Therefore, inclusive and data-based health policies, ongoing education, and financial support are needed to ensure equitable access. With a comprehensive systemic approach, CGM has the potential to revolutionize diabetes management towards a more preventive, personal, and sustainable paradigm in Indonesia..